Determinants of services FDI inflows in Asean countries - Kaliappana, Shivee Ranjanee; Khamis, Khamis Msellem; Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
Since 1990s, there has been tremendous increase in the movement of foreign direct investment (FDI) especially to developing countries. An interesting development in the international capital flows is that the FDI is increasingly shifting towards services industry in recent years. The main concern in this regards is whether developing countries would be able to attract the services-based FDI and get benefits from the inflows. This study empirically investigates the determinants of services-based FDI in ASEAN countries using a static linear panel data analysis. The data for the empirical estimation covers from 2000 until 2010. The empirical findings indicate that services FDI is positive and significantly determined by human capital, the availability of quality infrastructures, market size and trade openness, whereas inflation (proxy for macroeconomic stability) is found to be negative and insignificant. These findings reveals that ASEAN countries should focus on enhancing growth, stock of human capital, infrastructure * Corresponding Author: E-mail: shivee@upm.edu.my Any remaining errors or omissions rest solely with the author(s) of this paper. 46 International Journal of Economics and Management and promote more liberal trade policies in order to attract FDI in service sector.